Formation of professional competence of future specialists of economic specialties in ZVO - Dembitskaya, S.; Kobylyansky, A.; Pugach, S. (Scientific notes of the pedagogical department, 2021)
The article deals with the problem of the formation of professional competence of future specialists in economic specialties. The relevance of the presented research lies in the fact that the change of knowledge to competence-based methodological approach in higher education in accordance with global trends determines the need to develop the content of the concept of competence of future specialists in economic specialties. The purpose and objective of the article is to determine the structure of the professional competence of future specialists in economics, as well as the features of the formation of labor protection and legal competence of students of economic specialties as a component of their professional competence. To achieve the intended goal using such general research methods: generalization, comparison, systematization and abstraction. The structure of the professional competence of future specialists in economic specialties is substantiated, which contains the activity and personal components, and is determined by the requirements of employers for the qualifications of employees. The ways of improving the educational process in order to form the labor protection and legal competence of future specialists in economic specialties, as an important component of their professional competence, have been determined. In particular, such as: search and substantiation of theoretical and methodological foundations for the formation of legal and labor protection competence of future specialists-economists; motivation of students of economic specialties to study legal and security disciplines; study and adaptation of positive foreign experience, as well as the development of appropriate methodological support and the like. It was found that further research requires the definition and substantiation of psychological and pedagogical conditions for the implementation of the model of the formation of professional competence of students of economic specialties in vocational training in higher education institutions.